81 Evaluation of feeding immunoglobulin-Y to Holstein feeder cattle for the control of liver abscesses & reduction of macrolide-resistant bacteria dissemination. (28th November 2020) - Stotz, Miranda K
Abstract: Despite the regular use of macrolide-antibiotics in the diets of feedlot cattle, liver abscesses persist representing a financial burden to both pre- and post-mortem sectors of the beef industry. Alternative strategies, which simultaneously address liver infections and reduce the dissemination of antibiotic-resistant bacteria, are needed. An immunoglobulin-Y (IGY) product, developed to target Fusobacterium necrophorum andTrueperella pyogenes, was evaluated for the control of liver abscesses and its effect on macrolide-resistant Enterococcus growth from feces. Sixty-four Holstein steers (Initial BW= 384±13.5kg) consuming a finishing diet (90% concentrate) for 188 d (Final BW= 660±42 kg) were used in a completely randomized design where treatments included: TYL (Tylosin phosphate fed at 90 mg/hd/day; n = 32) or IGY (fed at 2.5g/hd/day; n = 32). Feed intake was recorded daily and BW was recorded every 28 d until slaughter. After 150 d on treatment fecal samples were randomly obtained from each treatment group four times (n = 40) and cultured on bile-esculine agar enriched with 8 μg/mL of erythromycin. Continuous variables of feedlot growth performance, carcass data and bacterial growth were analyzed using the MIXED procedure of SAS with the fixed effect of treatment and random effects of steer or sampling day, respectively. Ordinal carcass data was analyzed using the FREQ procedure of SAS observing the Cochran-Mantel-Haenszel value. Treatment did not affect DMI (P = 0.21), ADG (P = 0.50) or G:F (P = 0.36). Treatment neither affected hot carcass weight (P = 0.37) nor longissimus muscle area (P = 0.25). However, TYL resulted in greater back fat thickness than IGY (0.32 vs. 0.23 in.; P < 0.02) and consequently greater numerical yield grade (P < 0.02). Quality grade was not affected by treatment (P = 0.65). No treatment difference was observed for liver abscesses prevalence (TYL= 63% vs. IGY= 52%; P = 0.40) or severity (P = 0.23). There was a greater proportion of erythromycin-resistant Enterococcus growth for TYL than IGY (42.6 vs. 21.9%; P < 0.04). Specifically formulated IGY feed additives may be viable alternatives to antibiotics in the diets of feedlot cattle.